Islalink: A Web-Based Navigation, Booking and Tourism Guide for Santiago Island Travelers (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
For many years, traditional motorized boats (bangkero) and large transport barges have been the primary forms of public transportation connecting the mainland to Santiago Island in Bolinao, Pangasinan. However, managing these services presents significant difficulties due to their decentralized nature, lack of standardized booking, and heavy reliance on traditional cash fare and paper manifest collection methods. Enhancing fare collection, capacity management, and route information has become increasingly important to address the inefficiencies of these manual processes, such as payment delays, human transcription errors, and capacity uncertainties. This study developed IslaLink: A Web- based Navigation, Booking, and Tourism Guide for Santiago Island Travelers. This comprehensive system integrates automated booking. The system uses digital booking technology to streamline reservations, allowing passengers to confirm and pay for their slots electronically while enabling real- time manifest tracking and location information for operators and tourism staff. This digital integration significantly enhances transaction speed, data accuracy, and operational efficiency, ultimately transforming the island commuting and tourism experience. The study is intended for Santiago Island travelers and boat operators / stakeholders, aiming to implement technological solutions that optimize commuting and tourism operations, specifically along the Santiago Island transport routes within Bolinao, Pangasinan. The system enables travelers to effortlessly book slots digitally, which automatically calculates the fee and tracks capacity. This method removes the need for manual fare management, booking delays, and human mistakes. The study concludes with recommendations for future expansion and further improvements to enhance overall efficiency in public transportation and tourism management.